Sustainability Engineering for Enhanced Process Design and Manufacturing Profitability Balancing the Environment through Renewable Resources - Perl, Jeffery P. (Springer International Publishing : Imprint: Springer, 2024)
XXXIV, 268 p. 20 illus., 6 illus. in color.